Empirical study of black-scholes warrant pricing model on the stock exchange of Malaysia - Hong, Boon Kyun (2004)
This paper addresses the question of how well the best-known warrant/ option pricing model – the Black-Scholes model – work in the stock exchange of Malaysia. Results of most studies (Rubinstein, 1981; Geske, Roll, & Shastri, 1983; Scott, 1987) have been positive in that the Black-Scholes model generates warrant values fairly close to the actual prices at which warrants trade especially for shorter term maturity warrants. Nevertheless, some regular empirical failures of the model have been noted (Macbeth & Merville, 1980; Lauterbach & Schultz, 1990). The Black-Scholes model tends to overvalue ‘in-the-money’ warrants and undervalue ‘out-of-the-money’ warrants.